Studi Deskriptif Penggunaan Model Problem Based Learning terhadap Partisipasi Siswa dalam Pembelajaran Bahasa Indonesia di SMP - Yessica Rain Simanjuntak; Depitaria Br Barus; Perida Roma Asi Siahaan (Lembaga Yasin AlSys, 2026)
This study was motivated by the low level of student participation in Indonesian language learning, which remains teacher-centered, causing students to tend to be passive in the learning process. This study aims to describe the implementation of the Problem Based Learning (PBL) model and to analyze the improvement of student participation in Indonesian language learning on descriptive text material in Grade VIII of SMP Budi Setia Sunggal. This study used a qualitative approach with a descriptive research type. The study was conducted in the odd semester of the 2025/2026 academic year and involved 21 Grade VIII students as research subjects. Data were collected through observation, interviews, and documentation, and were then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that the implementation of the PBL model was able to increase student participation, as indicated by an increase in the number of active students from approximately 43% to 71%. Students became more active in group discussions, more confident in expressing opinions, and able to collaborate in completing learning tasks. However, some students still showed a lack of confidence when giving presentations in front of the class. The conclusion of this study affirms that the PBL model can create Indonesian language learning that is more active, interactive, and student-centered. These findings contribute to the development of innovative learning practices, particularly in increasing student participation in descriptive text material, and provide practical implications for teachers in designing more participatory learning strategies.